2005
DOI: 10.1128/aem.71.2.912-920.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-Aggregation and Inactivation of Poliovirus 1 in Groundwater Stored in a Hydrophobic Container

Abstract: Viral inactivation and adhesion-aggregation in water are often studied as separate phenomena. When the focus is placed on viral adhesion-aggregation, inactivation is neglected because the phenomena under investigation occur over a short period measured in days. When viral inactivation is studied, adhesion-aggregation phenomena are considered to be negligible because viral survival is traced over several days or months. In the present work, we took a global approach, examining the relative contributions of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 47 publications
(33 reference statements)
1
39
0
2
Order By: Relevance
“…These factors may induce viral inactivation, adhesion to support, and/or aggregation (11,13). Inactivation consists of a loss of viral infectivity and is the consequence of a modification/deterioration of the capsid or genome.…”
mentioning
confidence: 99%
“…These factors may induce viral inactivation, adhesion to support, and/or aggregation (11,13). Inactivation consists of a loss of viral infectivity and is the consequence of a modification/deterioration of the capsid or genome.…”
mentioning
confidence: 99%
“…When preparing artificially contaminated samples for the validation of our NV detection method in bottled water based on membrane filtration and real-time reverse transcription-PCR (RT-PCR) (16), we observed a substantial decrease of the viral load after a few days of storage. Since adsorption of human enteric viruses to the walls of different container materials had been reported previously (7,8,20,25,28), we suspected that a similar phenomenon was occurring in our samples. We therefore investigated whether enteric viruses may also adsorb to polyethylene terephthalate (PET) and glass bottles and to what extent such adsorption depends on the virus strain, the chemical composition of the water, and the presence of autochthonous microorganisms.…”
mentioning
confidence: 74%
“…Many studies conducted on the survival of enteric viruses in water indicated that the loss of virus titer occurs at a variety of rates (1,4,7,10,12,29). However, in several of these studies, loss of viruses due to adherence to the support was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…Pour qu'une désinfection soit efficace, un contact entre les désinfectants et les microorganismes est nécessaire. Par conséquent, les capacités des microorganismes à coloniser des particules et à s'agréger peuvent ainsi influencer l'action des désinfectants (CAMPER et al, 1986;GASSILLOUD et GANTzER, 2005;HOFF et AKIN, 1986;LECHEvALLIER et al, 1984;LEILEI et al, 2008;STEwART et al, 1990). D'autre part, le mode et le site d'action des désinfectants peuvent être aussi la cible de résistance chez certains microorganismes.…”
Section: La Diversité Des Espèces Microbiennes Dans L'eau Potableunclassified